1980
DOI: 10.3382/ps.0591460
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Biological Availability of Xanthophyll Within and Among Generic Sources

Abstract: Xanthophyll depleted, fasted broilers were intubated with various xanthophyll sources in a series of six experiments. The increase in serum xanthophyll per milligram xanthophyll intubated per kilogram body weight was used to estimate exahtnophyll availability. Statistically significant differences among samples within and among generic sources were obtained. As a result, beta-apo-8'-carotenoic acid ethyl ester (apo-EE) was used as a reference standard in Experiments 4 to 6. When the availability of apo-EE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…When laying hens were fed on a sorghum-soybean diet, carotenoids were not detected in their blood serum; however, inclusion of lutein at the level of 200 mg/kg in such a diet was associated with lutein concentration in serum of 18.25 mg/mL (Haq et al 1995). When the level of xanthophylls (as marigold meal) intubated to 46-d-old broilers was increased from 4.0 to 16.0 mg/kg body weight, serum xanthophyll concentration increased from 2.17 up to 3.13 and from 1.86 to 3.31, mg/mL after 18 and 28 h, respectively (Middendorf et al 1980). When the level of lutein diester supplementation in a chicken diet was increased from 5 up to 80 mg/kg, lutein concentration in serum increased only from 1.4 up to 9.5 (g/mL; Tyczkowski and Hamilton 1986).…”
Section: Discussionmentioning
confidence: 97%
“…When laying hens were fed on a sorghum-soybean diet, carotenoids were not detected in their blood serum; however, inclusion of lutein at the level of 200 mg/kg in such a diet was associated with lutein concentration in serum of 18.25 mg/mL (Haq et al 1995). When the level of xanthophylls (as marigold meal) intubated to 46-d-old broilers was increased from 4.0 to 16.0 mg/kg body weight, serum xanthophyll concentration increased from 2.17 up to 3.13 and from 1.86 to 3.31, mg/mL after 18 and 28 h, respectively (Middendorf et al 1980). When the level of lutein diester supplementation in a chicken diet was increased from 5 up to 80 mg/kg, lutein concentration in serum increased only from 1.4 up to 9.5 (g/mL; Tyczkowski and Hamilton 1986).…”
Section: Discussionmentioning
confidence: 97%
“…Even this small quantity of pigment represents a considerable cost for egg producers (Williams, 1992). Several researches have been carried out to seek improvements of pigmentation efficiency (Middendorf et al, 1980;Marusich & Baurenfeind, 1981). The synthetic pigment canthaxanthin (CTX) is found 1.5-5 times as potent as natural xanthophylls for the pigmentation of egg yolk (Akiba et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Component xanthophylls also are subject to both oxidative and enzymatic degradation and amounts present in dehydrated forage depend on how the cut forage is processed. Middendorff et al (1980) reported appreciable differences in the amount and biological availability of xanthophyll among dehydrated alfalfa meals. Middendorff (1980) also presented data that indicated that sun curing decreased the biological activity of xanthophyll in Coastal bermudagrass.…”
Section: Introductionmentioning
confidence: 94%